Temperature Dependence of AlGaN/GaN High Electron Mobility Transistors on 200 mm Si wafers - Junior, Braz Baptista [UNESP] (2022)
In this paper, the temperature dependence of AlGaN/GaN High Electron Mobility Transistors (HEMTs) on silicon substrates is studied experimentally. Drain current (ID), transconductance (gm), threshold voltage (VT) and drain-induced barrier lowering (DIBL) were analyzed in the temperature range from -35°C to 200°C. In addition, gate current (IG) and subthreshold slope (SS) were also analyzed in order to understand the physical mechanisms involved. The results indicate that gate current increases with increasing temperature. Also, as the gate current (IG) increases, the drain current (ID) decreases. The characteristics of AlGaN/GaN HEMTs on silicon substrates indicate that they may be a promising candidate for analog and radio frequency (RF) applications.